(untitled) (Journal of Science Foundation, 2015)
The fecundity and sex- ratio of 2200 Labeo bata (Hamilton) specimens were studied. The fecundity of 234 gravid females varied from 51,354( for a fish with total length of 127.3 mm and total body weight of 20.0 g) to 91,568( for a fish with total length of 256.6 mm and total body weight of 156.70g).The mean fecundity was recorded as 67,617.50±13,510.15 for the average length and weight of 192.98±41.06 mm and 87.79±49.07 g, respectively .The mean total length and weight of gonad was 67.62± 24.01 mm and 20.35±13.50 g, respectively .The relationship between fecundity ( F.) and other parameters such as total length ( TL ), Standard length ( SL), total weight( TW), gonadal length (GL), gonadal weight (GW) and gonadal depth (GD) were studied. DOI: http://dx.doi.org/10.3329/jsf.v11i2.21595 Journal of Science Foundation, 2013;11(2):43-48